Do ludu pracującego Wybrzeża. ([S.l. : s.n.], 1946)
Ulotka propagandowa nawołująca do głosowania 3xtak.
Keywords: Referendum -- Polska -- 1946 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne